Comparative Study of Employee Motivation for Those Working from Home Versus Those Working in the Office - Ngitung, Yosua Erich; Sanjaya, Regi (STIE Ekuitas, 2024)
Introduction/Main Objectives: Remote work has been one of the most effective solutions for companies during the recent pandemic. It has transformed our perspective on work by offering employees significant flexibility in both their work locations and schedules. Background Problems: With the pandemic now considered endemic, some individuals are choosing to return to the office, while others still prefer working from home. An employee's choice between office work and remote work is strongly tied to their work motivation. It is essential for companies to identify the factors driving these preferences to manage their employees effectively and efficiently. Novelty: The first comparative case study on employee motivation between remote work and office work in Indonesia's IT industry. Research Methods: This case study employs a qualitative approach, utilizing semi-structured interviews with six informants from an IT company. Finding/Results: Employees are more motivated when they work in the office compared to when they work from home, with office-based employees generally feeling more motivated due to factors like improved communication, tangible recognition, a stronger sense of achievement, better growth-supporting tools, and a more comfortable work environment. Conclusion: The research shows that working from the office is generally favored over working from home. However, the company should continue offering both options, not only due to the nature of the IT industry but also to combine the benefits of both in-office and remote work. leverage the benefits of both work environments.